The Effect of Using Quiz Media on Learners' Literacy Skills - Umi Anisa Aprilia (Science Center Group, 2024)
Background: The integration of digital game-based learning platforms in education has increasingly been recognized as an effective strategy to enhance student engagement and literacy development. Quizizz, as an interactive quiz-based application, offers real-time feedback and gamified learning experiences that may support the improvement of learners’ literacy skills. Objective: This study aimed to analyze the effect of using Quizizz media on learners’ literacy skills in secondary education. Methods: A quantitative quasi-experimental design with a non-equivalent control group was employed. Sixty students were selected through purposive sampling and divided into an experimental group, which received literacy instruction using Quizizz, and a control group, which received conventional instruction. Literacy skills were measured through validated pre- and post-tests assessing text comprehension, information analysis, and vocabulary mastery. Data were analyzed using independent samples t-tests to determine significant differences between groups. Results: The findings revealed a statistically significant difference in post-test literacy scores between the experimental and control groups (p < 0.05). Students exposed to Quizizz demonstrated greater improvement in text comprehension and vocabulary acquisition. Classroom observations indicated higher levels of engagement, motivation, and active participation in the experimental group. The real-time feedback feature facilitated immediate error correction and reinforced literacy learning. Conclusion: The use of Quizizz media significantly enhances learners’ literacy skills by promoting interactive engagement, immediate feedback, and gamified learning experiences. Integrating digital quiz-based platforms into literacy instruction provides an effective and motivating alternative to conventional teaching methods, although adequate technological infrastructure remains essential for optimal implementation.